2000
DOI: 10.1054/bjoc.2000.1108
|View full text |Cite
|
Sign up to set email alerts
|

Detailed deletion mapping of chromosome band 14q32 in human neuroblastoma defines a 1.1-Mb region of common allelic loss

Abstract: Neuroblastoma (NB) is a well-known malignant disease in infants, but its molecular mechanisms have not yet been fully elucidated. To investigate the genetic contribution of abnormalities on the long arm of chromosome 14 (14q) in NB, we analysed loss of heterozygosity (LOH) in 54 primary NB samples using 12 microsatellite markers on 14q32. Seventeen (31%) of 54 tumours showed LOH at one or more of the markers analysed, and the smallest common region of allelic loss was identified between D14S62 and D14S987. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 25 publications
4
21
0
Order By: Relevance
“…The deleted 14q11.2-13.1 and 14q32.1 regions have been implicated in various other human malignancies, including bladder (Chang et al, 1995), colorectal (Young et al, 1993), gastrointestinal (ElRifai et al, 2000;Debiec-Rychter et al, 2001), ovarian (Bandera et al, 1997), renal (Schwerdtle et al, 1997), neural carcinomas (Theobald et al, 1999;Hoshi et al, 2000), and NPC (Mutirangura et al, 1998). A radon-induced deletion region was detected around marker D14S306 in human bronchial cells, which is consistent with our current findings at the 14q11.2-13.1 region by this genetic complementary approach (Weaver et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The deleted 14q11.2-13.1 and 14q32.1 regions have been implicated in various other human malignancies, including bladder (Chang et al, 1995), colorectal (Young et al, 1993), gastrointestinal (ElRifai et al, 2000;Debiec-Rychter et al, 2001), ovarian (Bandera et al, 1997), renal (Schwerdtle et al, 1997), neural carcinomas (Theobald et al, 1999;Hoshi et al, 2000), and NPC (Mutirangura et al, 1998). A radon-induced deletion region was detected around marker D14S306 in human bronchial cells, which is consistent with our current findings at the 14q11.2-13.1 region by this genetic complementary approach (Weaver et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Isolation of the bacterial artificial chromosome clone and fluorescence in situ hybridization A genomic clone harboring AURKA was obtained by PCRbased screening of the CITB human bacterial artificial chromosome (BAC) library (Research Genetics, Huntsville, AL, USA) as described previously (Hoshi et al, 2000) with a paired primer set of 5 0 -AGCTCTGAGACACATGGCCT-3 0 and 5 0 -TGTGTGTCTGTCCGGCAC-3 0 specific for the sequence-tagged site of RH12027 existing on the 3 0 untranslated region of AURKA. Fluorescence in situ hybridization was performed using the BAC clones b57E22 and RMC20L116 harboring the centromeric sequence of chromosome 20, as described previously .…”
Section: Quantitative Real-time Pcr Assaymentioning
confidence: 99%
“…Loss of heterozygosity (LOH) and comparative genomic hybridization (CGH) studies of primary tissue have shown partial or complete loss of 14q, providing indirect evidence for the existence of TSGs on chromosome 14. Not only has this loss been found in esophageal squamous cell carcinoma (ESCC; Pack et al, 1999;van Dekken et al, 1999;Hu et al, 2000;Ihara et al, 2002), but it also has been found in a wide variety of other cancers including head and neck squamous cell carcinoma (Lee et al, 1997); gastrointestinal (El Rifai et al, 2000), breast (O'Connell et al, 1999), colorectal (Bando et al, 1999), bladder (Chang et al, 1995), renal (Schwerdtle et al, 1997), ovarian (Bandera et al, 1997), astrocytic (Hu et al, 2002) cancer; nasopharyngeal carcinoma (NPC; Mutirangura et al, 1998;Cheng et al, 2003); neuroblastoma (Takayama et al, 1992;Hoshi et al, 2000); and meningioma (Simon et al, 1995). Despite the growing evidence implicating chromosome 14 as having a role in cancer development, no single chromosome 14 TSG has yet been clearly identified because multiple large, nonoverlapping putative tumor-suppressive regions were found in previous studies.…”
Section: Introductionmentioning
confidence: 99%